PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MELALUI IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN PPKn DI SEKOLAH DASAR (Studi Literatur) - Radot Tua Joseph Marbun; Linda Zakiah; Juhana Sakmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the enhancement of elementary school students’ creative thinking skills through the implementation of the Project Based Learning (PjBL) model in Civic Education (PPKn) learning. The method used in this research is a literature review, examining various sources such as national journals, scientific articles, and relevant books. The results of the review indicate that the PjBL model is effective in developing students' creative thinking abilities, as it actively engages them in designing, executing, and reflecting on meaningful and contextual projects. In the context of Civic Education, this model encourages students to explore values such as nationalism, democracy, and social responsibility through real-life, collaborative activities. The characteristics of PjBL, which emphasize problem-solving, innovation, and product presentation, align with indicators of creative thinking such as fluency, flexibility, elaboration, and originality. Therefore, the implementation of Project Based Learning has the potential to be an alternative learning strategy that optimizes the development of creative thinking skills in Civic Education at the elementary school level.